Pengembangan Pemberdayaan Masyarakat melalui Program Kuliah Kerja Nyata di Desa Nalon Kecamatan Serbajadi - Syauki, Muhammad; Wahidah, Wahidah; Mirna, Mirna; Khairunnisa, Khairunnisa; Anggraini, Dea; Puspita, Ade Ayu; Balqis, Siti; Indah, Fauziah; Maolana, Bagas; Hadi Lubis , Irda Auliya; Zahra, Fatimah; Saputra, Wira Aditia; Sahara, Hertina; Ryamizar, M. (LSM Catimore dan Sahabat, 2024)
Community development through the Community Service Program (KKN) in Nalon Village, Serbajadi District, East Aceh, is a strategic effort to strengthen the capacity and welfare of the local community. This program is designed to facilitate the active participation of students in various empowerment activities, such as education, health, creative economy, and environmental conservation. Through a participatory and collaborative approach, students act as agents of change who help explore local potential and overcome challenges faced by society. The results of this program show that there is an increase in community awareness and skills in these fields, which has an impact on improving the quality of life and sustainability of development in Nalon Village. This KKN program is also a forum for students to apply the knowledge that has been obtained in college in a real context, as well as strengthen the relationship between universities and the community.